Text message reminders increased colorectal cancer screening in a randomized trial with Alaska Native and American Indian people. Issue 8 (21st December 2016) - Muller, Clemma J.; Robinson, Renee F.; Smith, Julia J.; Jernigan, Meghan A.; Hiratsuka, Vanessa; Dillard, Denise A.; Buchwald, Dedra
Abstract : BACKGROUND: Alaska Native and American Indian people (AN/AIs) have a high incidence of colorectal cancer (CRC) and CRC‐related mortality. Screening can prevent death from CRC, but screening rates are low in racially and ethnically diverse populations. The authors conducted a randomized controlled trial using text messaging to increase CRC screening among unscreened AN/AIs in a tribal health care system in Anchorage, Alaska. METHODS: The intervention entailed up to 3 text messages sent 1 month apart. The authors randomized 2386 AN/AIs aged 40 to 75 years who were eligible for CRC screening to the intervention or usual‐care control conditions. Screening status was ascertained from electronic health records 3 months and 6 months after the last text message. Hazard ratios (HRs) were estimated to evaluate the effectiveness of the intervention, stratified by age and sex. RESULTS: The intervention increased CRC screening for AN/AIs aged 50 to 75 years (HR, 1.42; 95% confidence interval [95% CI], 0.97‐2.09) and aged 40 to 49 years (HR, 1.24; 95% CI, 0.95‐1.62). Within both age groups, the HRs were higher for women (HR, 1.69 [95% CI, 1.02‐2.80] and HR, 1.37 [95% CI, 1.01‐1.88]) compared with men (HR, 1.09 [95% CI, 0.59‐1.99] and HR, 0.90 [95% CI, 0.54‐1.53]). Interaction analysis yielded P values of .55 and .09, respectively, for age and sex. CONCLUSIONS: A simple text messaging intervention was found to increase CRC screening rates in AN/AIs, a group with high CRC morbidity and mortality. Text messaging may be a cost‐effective means of reducing CRC screening disparities in AN/AIs and other populations. Cancer 2017;123:1382–1389. © 2016 American Cancer Society . Abstract : In the current study, text messages lead to a 42% higher colorectal cancer screening rate in a clinic‐based sample of Alaska Native and American Indian people aged 50 to 75 years. The intervention only appears to be effective in women, with no effect noted in men.